Survival of Radio-Marked Versus Leg-Banded Northern Bobwhite in Kentucky - Evan P. Tanner; Ashley M. Unger; Patrick D. Keyser; Craig A. Harper; Joseph D. Clark; John J. Morgan (National Quail Symposium Proceedings, 2017)
Understanding the impact of radiomarking northern bobwhite (Colinus virginianus) survival is essential because of the widespread reliance on radiotelemetry to assess vital population parameters. We conducted an assessment of bobwhite populations within the Central Hardwoods Bird Conservation Region using leg banding and radiotelemetry on Peabody Wildlife Management Area, a 3,330-ha reclaimed surface mine in western Kentucky. We captured bobwhites using baited funnel traps during a 112-day period (23 Jul-11 Nov 2010) and marked 180 with necklace-style radio-transmitters (6 g) and 256 birds with only leg bands. Eighty-five birds were opportunistically recaptured in funnel traps, of which 81 were used in developing survival estimates. We used the Cormack-Jolly-Seber model in Program MARK to estimate periodic survival rates (PSR) of both sample groups. Candidate models which included body mass as a covariate explained the most variability in survival. The estimated PSR was 0.309 6 0.109 based on the best approximating model and was 0.302 6 0.108 from model averaging. We calculated a point of inflection for this model, which suggested a mass ‘threshold’ of 131g, above which survival improved at a decreasing rate. The model including only the radio-transmitter effect had a DAICc .3 and was considered to be non-plausible. Further research with larger samples is needed to develop more robust survival models to fully assess the effects of radiomarking bobwhites. It does not appear, based on our study, that radio transmitters adversely affect survival of northern bobwhite.
Keywords: capture-recapture; Colinus virginianus; Cormack-Jolly-Seber; Kentucky; Program MARK; radiomarking; reclaimed mined land